Employee Empowerment in Enterprises Operating in the Business Services Industry - Deszczyński , Bartosz (Studia Oeconomica Posnaniensia, 2026)
The paper offers a discussion on the role of employee empowerment in relationship oriented companies. The theoretical part of the paper highlights the challenges in employee relationship management and brings a definition of the term empowerment and its impact on the company. An empirical exemplification of this phenomenon is based on the synthesis of nine shared services centers (SSC) and business process outsourcing (BPO) entities. The SSC/BPO industry was deliberately chosen as an already significant employer, which is still growing in importance in Poland and in Central and Eastern Europe. The main conclusion based on theoretical research presented in this paper is that employee empowerment is a major tool in the relationship management of a company. In turn, the empirical material proved that empowerment is being applied in the SSC/BPO industry. Still, a particular difficulty has been identified in its implementation in organizational structures other than the project teams, e.g. in traditional functional departments. This may result in higher employee attrition rates and lower work engagement.